2023
DOI: 10.3390/ijms24021328
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Bioactive Potential of Secondary Metabolites Isolated from Piper sarmentosum Roxb.

Abstract: Piper sarmentosum Roxb. (Piperaceae) is a traditional medicinal plant in South-East Asian countries. The chemical investigation of leaves from this species resulted in the isolation of three previously not described compounds, namely 4″-(3-hydroxy-3-methylglutaroyl)-2″-β-D-glucopyranosyl vitexin (1), kadukoside (2), and 6-O-trans-p-coumaroyl-D-glucono-1,4-lactone (3), together with 31 known compounds. Of these known compounds, 21 compounds were isolated for the first time from P. sarmentosum. The structures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 85 publications
(95 reference statements)
1
9
0
Order By: Relevance
“…Finally, Cluster VII is mostly represented by flavonoids (apigenin derivatives), including flavone- C -glycosides, and other phenolic metabolites such as phenylpropanoids and specific lignans. The compounds present in this cluster were found in relatively high amounts in leaves and are congruent with the constituents isolated from leaves of P. sarmentosum in our previous study [ 17 ].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, Cluster VII is mostly represented by flavonoids (apigenin derivatives), including flavone- C -glycosides, and other phenolic metabolites such as phenylpropanoids and specific lignans. The compounds present in this cluster were found in relatively high amounts in leaves and are congruent with the constituents isolated from leaves of P. sarmentosum in our previous study [ 17 ].…”
Section: Resultssupporting
confidence: 88%
“…Several previous studies on P. sarmentosum focused mainly on the constituents and pharmacological activities of the leaves [ 6 , 15 17 ]. Pharmacological studies recently conducted in Malaysia showed that the extract of P. sarmentosum leaves has vascular protective, neuroprotective, anti-obesity, and anti-hyperlipidemia activity [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…4) natural product (NP) or simple NP derivative, preferentially from plant or mushroom; 5) derived from a plant with reported Anti-Alzheimer or similar neurological activity, including such data from our previous research; or: from a compound class reported bene cial to neuro-in ammation; or: compound with structural similarity to such with reported activity in mental health [12,20,21,[24][25][26][27]. The tested natural products comprised a wide range of compound classes, including avonoids, alkaloids, lignans, anthraquinones, other diverse phenolics and triterpenoids.…”
Section: Resultsmentioning
confidence: 99%
“…According to the values of Δδ S-R of the (S) and (R)-MTPA esters, the absolute configuration at C5′ was concluded to be R. (Figure 3) During the purification of bioactive compounds from the n-BuOH extract of H. erinaceus, we obtained compound 5, and analysis of NMR data revealed that a structure of 5 might be 3- 4A,4B). This alkaloid was first isolated from the mealworm T. molitor, 16 and later from the leaves of P. erosus 17 and P. sarmentosum, 18 and the whole plants of H. cordata Thunb. 19 Compound 5 had identical 1 H and 13 C NMR data (DMSO-d 6 ) to those of the alkaloid from the mealworm (Table 2) as well as the published NMR data of the alkaloid from plants.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…erinaceus showed the most promising results, but there is little information available for breast cancer therapies using this mushroom. In this paper, we describe the isolation and structure elucidation of new geranyl-resorcinol derivatives and propose a structure revision of an alkaloid, 3-[2,3-dihydroxy-4-(hydroxymethyl)­tetrahydrofuran-1-yl]-pyridine-4,5-diol, previously isolated from the mealworm Tenebrio molitor, and later from the leaves of Pachyrhizus erosus and Piper sarmentosum, and the whole plants of Houttuynia cordata Thunb . Biological screening revealed potential drug candidates for breast cancer treatments.…”
Section: Introductionmentioning
confidence: 99%